Comparative analysis of the protective effects of melatonin and vitamin E on streptozocin-induced diabetes mellitus - Baydas, G; Canatan, H; Turkoglu, A (Blackwell Munksgaard, 2002)
There is a clearly documented link between diabetic complications and lipid peroxidation. Hyperglycemia causes a reduction in levels of protective endogenous antioxidants and increases generation of free radicals. The present Study was carried out to compare the protective effects of melatonin and vitamin E against streptozocin (STZ)-induced diabetes in rats. Melatonin was administered s.c. (100 mug/kg) whereas vitamin E was given i.p. (100 mg/kg) after induction of diabetes with STZ (60 mg/kg). Plasma total cholesterol, triglyceride and low density lipoprotein (LDL) levels were increased in STZ group while both melatonin and vitamin E injection caused a significant decrease in the levels of all these parameters. The lipid lowering effect of melatonin was greater than that of vitamin E. Melatonin caused a significant decrease in brain, liver and kidney tissue malondialdehyde (MDA) levels which were increased because of STZ-induced diabetes. Vitamin E also reduced elevated NIDA concentrations in diabetic rat tissues, but the effect of melatonin vas more potent than that of vitamin E. Furthermore, treatment of diabetic rats with melatonin increased brain and kidney glutathione peroxidase (GSH-Px) activity to the levels below that of control rats. Vitamin E was found to be less effective on GSH-Px activity levels in brain and kidney than melatonin whereas it was more potent than melatonin in liver. In summary, melatonin prevents many diabetic complications by reducing oxidative stress and protects organisms from oxidative damage and dyslipidemia. Considering the much lower molar concentration of melatonin compared with vitamin E, melatonin seems to be a more potent antioxidant, especially in the brain and kidney.
Keywords: diabetes mellitus; lipid peroxidation; melatonin; vitamin E